Stable isotope ratios of hydrogen separate mammals of aquatic and terrestrial food webs. Issue 11 (19th July 2015) - Voigt, Christian C.; Lehmann, David; Greif, Stefan
Summary: In food web studies, hydrogen stable isotope ratios (δ 2 H) are increasingly used as endogenous markers to quantify the relative importance of allochthonous input of organic material into aquatic ecosystems. Yet, it is unclear if differences in δ 2 H values between aquatic and terrestrial food webs translate into corresponding differences of δ 2 H values of vertebrate consumers. Using a triple‐isotope approach, we asked if fur keratin of 12 sympatric, non‐migratory bat species differ in stable isotope ratios (δ 2 HK, δ 13 CK, δ 15 NK ) according to the ecosystem (aquatic or terrestrial) in which they predominantly forage. We conducted a study with two captive species beforehand that suggested species‐specific differences in trophic discrimination for C and N, but not for H. In wild bats, stable isotope ratios of two Myotis species that trawl insects in aquatic habitats differed from those of four congeneric species that glean terrestrial insects by about 40‰ for H and by about 5‰ for N, indicating that both δ 2 HK and δ 15 NK values are useful for identifying membership of aquatic and terrestrial food webs. Further, we assessed the relative association of aerial‐hawking bat species to the terrestrial food web using trawling and gleaning bats as representatives of consumers in aquatic and terrestrial ecosystems, respectively. We found that the relative association of bats to terrestrial food webs varied largely among species, ranging from about 90% in Rhinolophus hipposideros to 43% in Eptesicus serotinus . Isotopic niche dimensions, as estimated by standardized ellipse areas using δ 2 HK and δ 15 NK values, varied largely among the 12 study species, with largest overlaps of isotopic niches among members of the aerial‐hawking bat ensemble. We conclude that δ 2 HK and δ 15 NK values are suitable parameters for evaluating the relative membership of mammals to aquatic and terrestrial food webs and also to evaluate isotopic niche dimensions and thus niche packing of species within consumer ensembles.